The spark of life: discharge physics as a key aspect of the Miller–Urey experiment - Longo, Savino (Frontiers in Physics, 2024)
The Miller-Urey experiment demonstrated the possibility of producing biomolecules from the chemical components of the primordial atmosphere, using an electric discharge. It profoundly influenced the development of prebiotic chemistry and astrobiology. The essential aspect of the experiment is the action of the electric field on a gaseous mixture, which produces chemically active species. These last react to ultimately form biomolecules. In this work the hypotheses and methods used to describe the chemical activation of a gas by an electric field, used in computational chemistry and in the physics of electrical discharges, are contrasted, showing that the second provides a much more realistic description of the primary events. A future model should combine the insights of the two communities to bring forth a faithful and insightful description of the experiment, from the primary events to the formation of biomolecules.